Technology and value. - Janeway, William H. (Social Research)
Part of a special issue on technology and culture. The writer considers the connection between technology and value. He identifies the relationship between technological leadership and the frontier between the public and private sectors. He calls into question the triumph of materialist rationality in this technical age, and he analyzes the relationship between the valuation of technology and the technology of valuation in an advanced capitalist regime.